MORPHOLOGICAL TYPOLOGY OF THE GORONTALO LANGUAGE: AFFIXATION AND REDUPLICATION IN AN AUSTRONESIAN LANGUAGE OF SULAWESI - Lamsike Pateda; Ibnu Rawandhy N. Hula; Ratni Bt. Hj. Bahri; Nur Hasaniyah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
The Gorontalo language, an Austronesian language spoken in Sulawesi, exhibits rich morphological processes that remain under-documented. As one of the regional languages of Eastern Indonesia, Gorontalo represents a crucial yet underrepresented component of Austronesian linguistic diversity, making its systematic description both timely and necessary. This study investigates its morphological typology, focusing on affixation, reduplication, and agglutinative structure to determine how words are formed and how the language fits within Austronesian morphological frameworks. The investigation is situated within contemporary debates in typology that view morphological systems as dynamic and sensitive to social and communicative pressures. While Gorontalo language is increasingly threatened by the dominance of Indonesian and declining intergenerational transmission, this research prioritizes structural analysis to capture its core morphological mechanisms before potential attrition accelerates. This urgency reflects broader concerns in language endangerment studies, where loss of morphology often precedes large-scale grammatical erosion. Employing a qualitative descriptive design, primary data were collected through field interviews with native speakers across various age groups and social backgrounds. The inclusion of multiple generations allows the study to capture ongoing morphological change alongside established usage patterns. Complementary data were drawn from oral narratives, traditional expressions, and informal conversations. Thematic analysis identified recurring morphological patterns, with attention to both form and sociocultural context. The analysis categorized affix types, examined reduplication functions, and assessed the degree of agglutination versus fusion in word formation. Results indicate that 18 active affixes (10 prefixes, 5 suffixes, and 3 confixes) were identified, demonstrating a highly productive system of affixation as the primary word-formation strategy. Reduplication functions flexibly, not only for plurality but also for aspect, intensity, and lexical derivation. Gorontalo displays predominantly agglutinative morphology, with clearly segmented morphemes combined cumulatively. However, morphophonemic fusion and simplified usage among younger speakers suggest a transitional typology, reflecting ongoing structural change. This study contributes empirical detail to Austronesian linguistics by documenting the morphological dynamics of an understudied language. These findings have direct pedagogical and typological implications, supporting language preservation initiatives, the development of local curricula, and the design of digital tools such, as morphological analyzers and learning applications. It challenges static typological classifications and offers practical insights for language preservation, local curriculum development, and digital documentation tool.